2020
DOI: 10.1136/annrheumdis-2020-217454
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine and O-GlcNAcylation: a novel immunometabolic therapeutic target for OA and chronic, low-grade systemic inflammation?

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…It is worth mentioning that, in addition to the well-known role of its participation in the synthesis of components of the extracellular matrix [1,30], GlcN is the precursor of N-Acetyl-glucosamine which is added to serine and threonine residues of nuclear and cytoplasmic proteins in the O-GlcNAcylation posttranslational modi cation [31]. O-GlcNAcylation plays a critical role in the regulation of both cellular homeostasis, in response to nutritional or hormonal cues, but also in response to stress or damage [32]. A recent study reported that an increase of global O-GlcNAcglycosylation occurs during the early stages of osteoblast differentiation in MC3T3-E1 cells, but not during osteoclastic differentiation of RAW264 cell line [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that, in addition to the well-known role of its participation in the synthesis of components of the extracellular matrix [1,30], GlcN is the precursor of N-Acetyl-glucosamine which is added to serine and threonine residues of nuclear and cytoplasmic proteins in the O-GlcNAcylation posttranslational modi cation [31]. O-GlcNAcylation plays a critical role in the regulation of both cellular homeostasis, in response to nutritional or hormonal cues, but also in response to stress or damage [32]. A recent study reported that an increase of global O-GlcNAcglycosylation occurs during the early stages of osteoblast differentiation in MC3T3-E1 cells, but not during osteoclastic differentiation of RAW264 cell line [33].…”
Section: Discussionmentioning
confidence: 99%
“…65 Further studies are encouraged in order to confirm these promising findings, since in the UK Biobank the data are reported for different glucosamine preparations and not specifically for GS. Regarding the mechanisms of action that can justify these epidemiological findings, we can argue that GS may interfere with some pro-inflammatory pathways such as nuclear factor kappa-B, mitogenactivated protein kinase and phosphatidyl-inositol-3-kinase-dependent pathways 66,67 that are usually involved in the pathogenesis of diabetes. 68 Finally, our umbrella review is, in our opinion, important since GS use was associated with a similar incidence in adverse effects, compared with placebo, suggesting that its use is safe.…”
Section: Authormentioning
confidence: 99%
“…2 Our editorial made some hypothetical considerations about the mechanism of action of this compound. 3 The editorial also commented on the difficulty of detecting a beneficial effect of glucosamine in OA, due to the modesty of the therapeutic effect, as well as the weakness of the methodological tools employed in OA clinical trials. 3 In some way, the relationship between glucosamine and OA takes us fully into the pathophysiology that revolves around immunometabolic regulation, a driver that can account for tissue deterioration in various chronic diseases and still with many aspects to be elucidated.…”
mentioning
confidence: 99%
“…3 The editorial also commented on the difficulty of detecting a beneficial effect of glucosamine in OA, due to the modesty of the therapeutic effect, as well as the weakness of the methodological tools employed in OA clinical trials. 3 In some way, the relationship between glucosamine and OA takes us fully into the pathophysiology that revolves around immunometabolic regulation, a driver that can account for tissue deterioration in various chronic diseases and still with many aspects to be elucidated. The hexosamine biosynthesis pathway (HBP), through which glucosamine can be metabolised in the cell, integrates the main cellular metabolic molecules, such as carbohydrates, amino acids, lipids and nucleotides, and regulates the inflammatory response through many mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation